2021
DOI: 10.1002/hep.31685
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the De Novo Purine Synthesis Pathway Through Adenylosuccinate Lyase Depletion Impairs Liver Cancer Growth by Perturbing Mitochondrial Function

Abstract: Background and Aims Hepatocellular carcinoma (HCC) is among the most common cancer types worldwide, yet patients with HCC have limited treatment options. There is an urgent need to identify drug targets that specifically inhibit the growth of HCC cells. Approach and Results We used a CRISPR library targeting ~2,000 druggable genes to perform a high‐throughput screen and identified adenylosuccinate lyase (ADSL), a key enzyme involved in the de novo purine synthesis pathway, as a potential drug target for HCC. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…2A ). Recent studies showed that purine metabolism is linked to liver tumor growth [ 57 ] and glioblastoma radiation resistance [ 58 ]. Our data indicate that purine metabolism is relevant to acquiring drug tolerance to EGFR TKIs in lung cancer.…”
Section: Resultsmentioning
confidence: 99%
“…2A ). Recent studies showed that purine metabolism is linked to liver tumor growth [ 57 ] and glioblastoma radiation resistance [ 58 ]. Our data indicate that purine metabolism is relevant to acquiring drug tolerance to EGFR TKIs in lung cancer.…”
Section: Resultsmentioning
confidence: 99%
“…[ 33 ] Another study suggested that adenylosuccinate lyase (ADSL) is the key enzyme involved in purine metabolism and mitochondrial function during the formation of liver cancer. [ 34 ] Liver cancer cells like many other cancer cells are addicted to glutamine. A chemical library screening of 13 compounds identified glutamine transporter inhibitor targeting alanine‐serine‐cysteine transporter, type‐2 (ASCT2, encoded by gene SLC1A5), V‐9302, showed the greatest synergism with GLS inhibitor, CB‐839, in suppressing HCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…MAPRE1 promotes cell cycle progression in hepatocellular carcinoma cells by interacting with CDK2 [31] . Adenylosuccinate lyase (ADSL), a key enzyme involved in the de novo purine synthesis pathway, has been shown to be a potential drug target in HCC [32] . At present, there is no research on AP3B1 and RNP1 in liver cancer, which is worth exploring.…”
Section: Discussionmentioning
confidence: 99%